THE ROLE OF ACADEMIC LIBRARIES IN FACILITATING POSTGRADUATE STUDENTS’ RESEARCH - Rasul, Aamir; Singh, Diljit (Malaysian Journal of Library and Information Science, 2010)
Universities are seeking to play a key role in the research and development process. An important element in the research process is the accessibility of information resources and services provided by libraries. Postgraduate students are key producers of research in universities, and an important element in their research process is the access to information. This study examines postgraduate students’ views on the role of the academic library services in facilitating their research and their satisfaction with the sources and services currently provided. Data was collected from 375 randomly selected postgraduate students in four Malaysian public universities. The findings show that the majority (90.1%) of respondents acknowledged the important role of library in facilitating research, and 72.5% of the respondents were satisfied with the current role being played by the libraries. However, certain areas needed to be improved such as longer opening hours for physical visits, in spite of the facilities for remote access assistance for supporting students’ research. The findings will be useful to academic libraries in providing better services to postgraduate students for their research.